UNDERSTANDING ENVIRONMENTAL IMPACT AND SUSTAINABILITY IN CEMENT PRODUCTION (Multidisciplinary Journal of Science and Technology, 2024)
This article explores the environmental impact and sustainability considerations in cement production using the IMRAD method, emphasizing the Introduction, Methods, Results, and Discussion aspects. Cement, a vital construction material, has faced growing scrutiny due to its significant environmental footprint. We delve into the challenges, methodologies, findings, and discussions surrounding sustainability initiatives within the cement industry.